2015
DOI: 10.17795/mejrh-25589
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Hippocampal Neuronal Numbers in Morphine-Dependent Rats by Voluntary Exercise Through a Brain-Derived Neurotrophic Factor-Mediated Mechanism

Abstract: Background: Exposure to morphine decreases neurogenesis in the hippocampus. Recent studies have shown that voluntary running decreases the severity of anxiety behaviors and cognitive deficits, and increased synaptic plasticity in morphine-dependent rats. Objectives: This study aimed to investigate whether the morphine dependence-induced attenuation of hippocampal neuron number in rats would be reversed by voluntary running through a brain-derived neurotrophic factor (BDNF)-mediated mechanism. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Our findings are similar to many studies 23 , 25 , 26 providing evidence that exercise can increase the BDNF and TrKB levels in hippocampus of morphine-dependent rats. Identical to previous studies, 27 , 28 our study supported that BDNF acts via the TrKB receptor is an important mediator between exercise and neural functions and play a key role in cell survival, neurite outgrowth, function of adult neurons, differentiation of developing neurons, learning and memory for morphine administration, 29 and protects against neurodegenerative disorders.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are similar to many studies 23 , 25 , 26 providing evidence that exercise can increase the BDNF and TrKB levels in hippocampus of morphine-dependent rats. Identical to previous studies, 27 , 28 our study supported that BDNF acts via the TrKB receptor is an important mediator between exercise and neural functions and play a key role in cell survival, neurite outgrowth, function of adult neurons, differentiation of developing neurons, learning and memory for morphine administration, 29 and protects against neurodegenerative disorders.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, exercise training facilitates the induction of LTP by lowering the LTP induction threshold [33]. Regular exercise training prevents the decrement of the hippocampal DG neuron numbers induced by the injection of morphine through a brain-derived neurotrophic factor (BDNF)-mediated mechanism [36].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of GABAergic receptors in the basolateral amygdala raises the probability of their role in memory storage in this region. Rashidy-Pour et al (2015) studied the role of the GABAergic system in acquiring, consolidating, and retrieving the newly learned information in the spatial avoidance learning model, and observed that parenteral GABA agonist (muscimol) significantly impaired the storage and retrieval of spatial memory (Rashidy-Pour, Vafaei, 2001). (Mansouri et al 2014) studied the potential mechanism of gallic acid anxiolytic effects in rat using plus maze test.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrophen enhances the viability and regeneration of the neurons, causes enhancement, stimulation, and growth of these cells, and is essential for memorization and memory (Maass et al, 2016). Neurotrophic factors such as brainderived neurotrophic factor (BDNF), nerve growth factor, and fibroblast growth factor contribute to support and growth of different types of cerebral neurons (Rashidy-Pour, Fathollahi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation